Elitism for sale: Promoting the elite school online in the competitive educational marketplace. (August 2013) - Drew, Christopher
Australia's neoliberal education agenda drives a competitive market climate where schools compete for potential clientele. In this climate, school impression management and self-promotion has become an important factor in maintaining a financially viable school. Schools produce image management texts including school prospectuses, newspapers advertisements, and school websites. Examining fifteen elite school websites from New South Wales Australia, this paper argues that the websites construct elite ideological discourses in order to position themselves as desirable within the neoliberal education context. The placement of promotional images and hyperlinks in salient places on the websites reveals the importance of self-promotion and the production of images of elitism in the marketised education climate. The school websites examined are found to have multiple animated and interactive functions that are used in the promotion of the schools as elite.